PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 56 PEKANBARU - Hafsari, Dwi; Marhadi, Hendri; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was result of IPS fourth graders of SDN 56 Pekanbaru still low with average value of 67.07 with KKM 75. This research aims to improve student achievement the fourth grade SDN 56 pekanbaru with the implementation of cooperative learning model student facilitator and explaining. This research was conducted during the second semester of the academic year 2015/2016, with 28 students research subjects consisted of 15 male students and 13 female students. This reseach was classroom action research with two cycles, every cycle consisting of two meetings and one daily tests. Data and research instruments consisted of a learning device (syllabus, lesson plan, student worksheets), and data collection instruments such as observation sheets teachers and students as well as achievement test in the form of daily tests. Teachers activities at the first cycle of the first meeting with percentage of 75% (good categories), the second meeting becomes 79.17% (good categories). The first meeting of the second cycle with the percentage of 83.33% (very good category), at second meeting be 91.67% (very good category). Students activities at the first cycle of the first meeting with percentage of 75% (good category), at second meeting be 79.17% (good category). Students activities in the first cycle of the first meeting with percentage of 87.50% (very good category), at second meeting be 91.67% (very good category). Before the implementation of cooperative learning model student facilitator and explaining with KKM 70, average value of base score 67.07, after the implementation of this model average value of the first cycle increased to 76.60, with the increased in 9.53 (14.20%), while the second cycle of average value of students be 82.41 with an increased be 15:34 (22.87%).Key Words : Cooperative Type Student Facilitator and Explaining, Result of IPS